2013
DOI: 10.1155/2013/879696
|View full text |Cite
|
Sign up to set email alerts
|

Extract ofRhus vernicifluaBark Suppresses 2,4-Dinitrofluorobenzene-Induced Allergic Contact Dermatitis

Abstract: Rhus verniciflua Stokes (RV) has traditionally been used as a food supplement and a traditional herbal medicine for centuries in Korea. Recent studies suggest that RV has potent antioxidative, antitumor, and anti-inflammatory properties. In this study, the anti-inflammatory effects of RV from mice sensitized with 2,4-dinitrofluorobenzene (DNFB) and activated macrophages were investigated. The results showed that RV reduced ear swelling and hyperplasia of ear tissue as well as an increase in vascular permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…19 Given that the pullulan hydrogels can let a pharmaceutic to be loaded into the hydrogels without any substantial chemical interaction, we hypothesized that pullulan hydrogels loaded with a certain herbal extract that shows antipruritic and anti-inflammatory effects might further augment the therapeutic effect on AD. 20 Among the herbal candidates, the Rhus verniciflua extract (RVE) was selected for a pharmaceutic to be loaded in the hydrogels in this study. Rhus verniciflua is an Asian tree species of the genus Toxicodendron, native to China and the Indian subcontinent, and cultivated in regions of China, Korea, and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…19 Given that the pullulan hydrogels can let a pharmaceutic to be loaded into the hydrogels without any substantial chemical interaction, we hypothesized that pullulan hydrogels loaded with a certain herbal extract that shows antipruritic and anti-inflammatory effects might further augment the therapeutic effect on AD. 20 Among the herbal candidates, the Rhus verniciflua extract (RVE) was selected for a pharmaceutic to be loaded in the hydrogels in this study. Rhus verniciflua is an Asian tree species of the genus Toxicodendron, native to China and the Indian subcontinent, and cultivated in regions of China, Korea, and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Where, 0 was absent and 4 was severe pinkish-red color of the ear. Ear thickness was measured before application (challenge) and then pre-and post-application [13].…”
Section: Induction Of Allergic Contact Dermatitis (Acd) With Dinitrofmentioning
confidence: 99%
“…The bark of Rhus verniciflua Stokes (RVS), or Toxicodendron vernicifluum, which belongs to the Anacardiaceae family, is used as food additive and herbal medicine for inflammatory disorders and cancer in Eastern Asia. RVS demonstrates various biological activities, including anti-oxidant, anti-inflammatory, neuroprotective, and anti-cancer effects, and some of which have been verified in vitro [16][17][18][19][20][21][22][23]. At the cellular level, RVS extract and its phenol-rich fraction inhibit lipopolysaccharide (LPS)-induced TNF- and IL-6 expression in RAW264.7 cells, a mouse macrophage cell line [17][18][19]23].…”
Section: Introductionmentioning
confidence: 95%
“…Fisetin, butein, and sulfuretin are the known anti-inflammatory polyphenols present in RVS [24][25][26]. Animals orally administered RVS extract exhibit reduced edema in chemically-induced dermatitis models [18,23], but whether this anti-inflammatory effect occurs in macrophages following oral administration of RVS extract has not been determined. A pharmacokinetic profile study showed that the majority of fisetin, sulfuretin, and other polyphenols in RVS extract were present in blood in their conjugated forms [27].…”
Section: Introductionmentioning
confidence: 99%